Laparoscopy versus laparotomy in the management of ectopic pregnancy with massive hemoperitoneum. Issue 2 (30th July 2013) - Cohen, Aviad; Almog, Benny; Satel, Abed; Lessing, Joseph B.; Tsafrir, Ziv; Levin, Ishai
Abstract: Objective: To compare the safety and feasibility of operative laparoscopy versus laparotomy in women with ruptured ectopic pregnancy and massive hemoperitoneum. Methods: In a retrospective cohort study at a university‐affiliated medical center, records of women with ruptured ectopic pregnancy and massive hemoperitoneum (> 800 mL) were reviewed. Results: Sixty women were diagnosed with ruptured ectopic pregnancy and massive hemoperitoneum: 48 underwent emergency laparoscopy; 12 underwent emergency laparotomy. There was no difference in hemodynamic status at presentation between the groups. Median operating time was significantly shorter in the laparoscopy group (50 minutes [range, 43–63 minutes] vs 60 minutes [range, 60–72 minutes]; P = 0.01). Median intra‐abdominal blood loss was significantly greater in the laparotomy group (1500 mL [range, 1400–2000 mL] vs 1000 mL [range, 800–1200 mL]; P = 0.002). There was no difference between the groups regarding treatment with blood products, perioperative complications, and hospitalization period. Conclusion: In patients with ruptured ectopic pregnancy and massive hemoperitoneum, laparoscopy is feasible and safe, with significantly shorter operating times compared with laparotomy. While the mode of surgery should be based on the surgeon's experience and preference, the significantly lower hemoperitoneum volume associated with laparoscopy may be a reflection of shorter operating times and quicker hemorrhage control.